Schaumburg family papers
Commission (1795 August 27) signed by Timothy Pickering and George Washington appointing Bartholomew Schaumburgh captain in the U.S. Army; and photocopies of passes (1865), one signed by Abraham Lincoln and the other by G. T. Beauregard, issued to Orleana Christy Schaumberg.
In part, positive and negative photocopies.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beauregard, G. T. -- 1818-1893.; Lincoln, Abraham, -- 1809-1865.; Pickering, Timothy, -- 1745-1829.; Schaumberg, Orleana Christy; Schaumburgh, Bartholomew, -- -1835.; Schaumburg family; Washington, George, -- 1732-1799.; United States. -- Army -- Officers; United States -- History -- Civil War, 1861-1865